Normalizing JMJD6 Expression in Rat Spinal Dorsal Horn Alleviates Hyperalgesia Following Chronic Constriction Injury - Mo, Cheng; Xu, Mengyuan; Wen, Cen; Chang, Ruimin; Huang, Changsheng; Zou, Wangyuan; Zhu, Xiaoyan; Guo, Qulian (Frontiers in Neuroscience, 2018)
Jumonji domain-containing protein 6 (JMJD6) is a homolog of hypoxia-inducible factor (HIF) asparaginyl hydroxylase, an inhibitor of HIF. HIF-1α is known to participate in neuropathic pain (NPP) during chronic constriction injury (CCI); however, the roles of JMJD6 in NPP have not been systematically investigated. In this study, we examined the temporal distribution and cellular location of JMJD6 in the spinal cord during CCI. In addition, we assessed behavioral changes representative of NPP in rats. Following CCI, lentiviral vectors (LV-JMJD6) were intrathecally administered to observe the changes in the expression of JMJD6, HIF-1α, and its downstream factor caspase-3. Co-immunoprecipitation was used to detect potential interactions between JMJD6 and HIF-1α. We found that JMJD6 was decreased in rats following CCI, which was accompanied by significant NPP–associated behavioral changes. JMJD6 was mainly expressed in neurons. Intrathecal injection of LV-JMJD6 following CCI alleviated the thermal and mechanical hyperalgesia, normalized JMJD6 protein expression, and decreased HIF-1α protein expression with a corresponding reduction in caspase-3 protein expression. Furthermore, the co-immunoprecipitation analyses showed that JMJD6 and HIF-1α protein immunoprecipitated with each other, indicating an interaction between these two proteins. Taken together, the results suggest that JMJD6 may serve as a sensor in neurons of the adult rat spinal cord during the CCI state. Furthermore, JMJD6 may exert its function in NPP by regulating HIF-1α in rats exposed to CCI.